Selective serotonin reuptake inhibitors or serotonin-norepinephrine reuptake inhibitors in pregnancy: Infant and childhood outcomes - Hendson, Leonora (Paediatr Child Health, 2021)
This position statement provides guidance for the monitoring, care, and follow-up of newborns exposed to selective serotonin reuptake inhibitors (SSRIs) or serotonin-norepinephrine reuptake inhibitors (SNRIs) in utero. Depression and anxiety are common during pregnancy and postpartum. While there are risks to taking medications during pregnancy, untreated or incompletely managed depression and anxiety also carry risks for the newborn. Poor neonatal adaptation syndrome (PNAS) occurs in one-third of newborns exposed to SSRIs or SNRIs in utero, and is generally mild and self-limiting. The low levels of SSRIs and SNRIs excreted in breast milk are compatible with breastfeeding. Persistent pulmonary hypertension of the newborn and congenital heart defects are rare associations of exposure to SSRIs or SNRIs in utero. There are inconsistencies in the literature regarding neurodevelopmental outcomes, specifically autism spectrum disorder and attention-deficit hyperactivity disorder. The inconsistencies likely relate to other factors (i.e., genetics, maternal depression, lifestyle, and comorbidities), rather than exposure to SSRIs or SNRIs in utero. Health care providers and parents should be reassured that PNAS is generally treatable with nonpharmacological measures, and that the risk of serious adverse effects from exposure to SSRIs or SNRIs in utero is low.